HARMONISM THE JURISPRUDENCE OF JA'FARI AND HANAFI: HISTORICAL STUDY AND BOTH LEGAL SOURCES (HARMONISME FIKIH JA'FARI DAN HANAFI: KAJIAN HISTORIS DAN SUMBER-SUMBER HUKUM KEDUANYA) - Lufaefi Lufaefi (al-Afkar, Journal For Islamic Studies, 2019)
The debate around Sunni and Shia, in addition to the issue of post-Rasulullah leadership, is also in the matter of Shari'a law between the two. It is not uncommon for the debate to arise in conflict at the epistemological level, even at the level of axiology. But actually, both of them have similar points that cannot be denied by each other. This article will describe Sunni-Shi'a historical sources in fiqh issues, sources used by both and what are the legal products produced through these sources. By comparing between Jurisprudence of Ja'fari (Syiah) and Hanafi (Sunni), this paper tries to find Sunni-Shia meeting points in the matter of its Shari'a. Perdebatan seputar Sunni dan Syiah, selain dalam persoalan kepemimpinan pasca Rasulullah, juga dalam persoalan hukum syariat antar keduanya. Tidak jarang perdebatan tersebut memunculkan pertikaian baik dalam tataran epistemologi, bahkan pada tingkat aksiologi. Namun sebenarnya, keduanya memiliki titik-titik persamaan yang tidak bisa dinafikan satu sama lainnya. Tulisan ini akan menjabarkan sumber historis Sunni-Syiah dalam persoalan fikih, sumber-sumber yang digunakan keduanya dan apa saja produk hukum yang dihasilkan melalui sumber-sumbernya itu. Dengan membandingkan antara Fikih Ja’fari (Syiah) dan Fikih Hanafi (Sunni), tulisan ini mencoba menemukan titik temu Sunni-Syiah dalam persoalan syariatnya.